Aims as a forming factor of production (construction) organization - Savenko, V.; Klyueva, V.; Nesterenko, I.; Palchik, S.; Pobeda, S. (Ways to Improve Construction Efficiency, 2019)
The activity of each element of the organization: managers, performers – actors and actors of the organization carries teleonomy, that is, expediency. In the target structure of organizations for its survival, preservation of balance, stability arise the need to solve special tasks to achieve internal and external security. The model of activity of an industrial complex always includes the object of management and the subject of management in the form of appropriate systems. Despite the fact that at the present stage information technologies are considered as intelligent information tools and technologies, and how, the intelligence of the control subject and the intelligence embedded in the information technology correlate with each other.